Kinetics of Cd(ii) adsorption and desorption on ferrihydrite: experiments and modeling. Issue 6 (15th May 2018) - Liang, Yuzhen; Tian, Lei; Lu, Yang; Peng, Lanfang; Wang, Pei; Lin, Jingyi; Cheng, Tao; Dang, Zhi; Shi, Zhenqing
Abstract : This study provided modeling tools to quantitatively assess the contributions of individual ferrihydrite binding sites to overall Cd(ii ) adsorption/desorption rates. Abstract : The kinetics of Cd(ii ) adsorption/desorption on ferrihydrite is an important process affecting the fate, transport, and bioavailability of Cd(ii ) in the environment, which was rarely systematically studied and understood at quantitative levels. In this work, a combination of stirred-flow kinetic experiments, batch adsorption equilibrium experiments, high-resolution transmission electron microscopy (HR-TEM), and mechanistic kinetic modeling were used to study the kinetic behaviors of Cd(ii ) adsorption/desorption on ferrihydrite. HR-TEM images showed the open, loose, and sponge-like structure of ferrihydrite. The batch adsorption equilibrium experiments revealed that higher pH and initial metal concentration increased Cd(ii ) adsorption on ferrihydrite. The stirred-flow kinetic results demonstrated the increased adsorption rate and capacity as a result of the increased pH, influent concentration, and ferrihydrite concentration. The mechanistic kinetic model successfully described the kinetic behaviors of Cd(ii ) during the adsorption and desorption stages under various chemistry conditions. The model calculations showed that the adsorption rate coefficients varied as a function of solution chemistry, and the relative contributions of the weak and strong ferrihydrite sites for Cd(ii ) binding varied with time at different pH and initial metal concentrations. Our model is able to quantitatively assess the contributions of each individual ferrihydrite binding site to the overall Cd(ii ) adsorption/desorption kinetics. This study provided insights into the dynamic behavior of Cd(ii ) and a predictive modeling tool for Cd(ii ) adsorption/desorption kinetics when ferrihydrite is present, which may be helpful for the risk assessment and management of Cd contaminated sites.